Some are smarter than others : the history of Marcos' crony capitalism - Manapat, Ricardo (New York : Aletheia Publications, 1991)
This book then comes as a way of fulfilling these promises. While the present work has its obvious imperfections, it hopefully has improved upon the original work both in terms of its coverage and social and political perspective.
I. The worship of BAAL: an initial look at Marcos Wealth -- II. The development of crony capitalism -- III. The relatives and cronies -- IV. The overseas empire -- V. In Lieu of a conclusion: Of Typewriters and flags.
Keywords: CAPITALISM -- PHILIPPINES